Direct and Off-Target Effects of ATP-Sensitive Potassium Channels Opener Diazoxide: A 2020 Update - Olga V. Akopova (Technological Innovation in Pharmaceutical Research Vol. 2, 2021)
Diazoxide (DZ) is a well known cardioprotective drug capable of mimicking ischemic preconditioning. Being primarilly a pharmacological opener of mitochondrial ATP-sensitive potassium channels (mKATP channels), DZ is known to produce multiple side effects because of its interactions with different cellular targets (such as plasma membrane KATP channels, F0F1 ATP synthase, succinate dehydrogenase and others), capable of confounding an understanding of direct bioenergetic effects of mKATP channels opening in mitochondria. In this review direct and off-target effects of DZ were discussed. The emphasis was made on molecular basis of DZ interaction with KATP channels and different KATP channels isoforms sensitivity to this drug. The present knowledge on DZ interaction with mKATP channels is outlined as well as DZ interactions with other molecular targets affecting mitochondrial functions and bioenergetics. Conclusion was reached that high sensitivity of mKATP channel to DZ shown in our studies allows for avoiding off-target effects of this drug in studies on isolated mitochondria, which makes it a useful tool for an appraisal of diverse functional effects of mKATP channel opening.